The Application of Good Governance Principles in Regional Financial Management at the Regional Financial and Asset Management Agency (BPKAD) of Maluku Province - Mahrani Mahrani; Normawati Normawati; Wahab Tuanaya; Safrudin Bustam Layn (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This research examines the application of good governance principles in financial management at the BPKAD of Maluku Province, focusing on public participation, transparency, accountability, effectiveness, efficiency, and the rule of law. Conceptually, governance is understood as a collaborative process between the state and non-state actors, with key principles emphasizing transparency, accountability, participation, rule of law, effectiveness, and efficiency. The legal framework refers to Law 17/2003, Law 1/2004, Government Regulation 12/2019, and Minister of Home Affairs Regulation 77/2020. The method used is qualitative, based on interviews, observations, and document analysis, and is analyzed using the interactive model of Miles, Huberman, and Saldana. The study results show that the implementation of good governance has been normatively pursued through the digitization of the financial system, the application of e-budgeting and e-procurement, and BPK supervision. However, practices remain predominantly procedural: low fiscal independence, routine spending dominance, weak audit follow-up, limited public literacy, and participation tends to be formalistic as per Arnstein's concept of tokenism. Obstacles are also related to technological readiness, the apparatus's capacity, and the pattern of incremental budgeting. In conclusion, the regional financial governance in Maluku shows structural progress but is not yet substantively optimal. Strengthening human resource capacity, consistency in law enforcement, expanding participation channels, and accelerating digitalization are necessary to enhance fiscal integrity and promote public financial reform in the context of regional autonomy.